Assisting Caregivers with Frail Elderly in Alleviating Financial Hardships. Issue 6 (18th August 2018) - Wang, Ming-Sheng; Wu, Chi-Fang
ABSTRACT: Many caregivers of individuals who are frail and elderly face financial hardships that have negative consequences that compound over time. This article explores the causes of these hardships, reviews Medicaid home and community-based interventions, and related government financial supports that have been used to alleviate them and concludes with recommendations for social work practice and social policy.